Une lecture du travail bénévole des chasseurs en termes de services - Olivier Aznar; Geneviève Brétière (VertigO, 2010)
We examined services provided by the voluntary work of hunters. What are common voluntary activities of hunters, and what are the economic indicators of these activities? We propose a method tested in five territories in France. We found that the majority of the voluntary work is consisted of protecting wild fauna, maintaining the natural environment and providing sociocultural activities. We discuss the beneficiaries of these activities and conclude that volunteers are motivated to provide services in order to maintain good hunting conditions.